THE KINSHIP GREETING OF THE SUSUPU COMMUNITY IN WEST HALMAHERA REGENCY - Rahma Djumati; Farida Maricar (Universitas Negeri Makassar, 2022)
This study aimed to describe many greetings forms found in Susupu community. The research method applied in this study was a descriptive qualitative method, because this study described data by words not numbers. This research was conducted in Susupu village, West Halmahera regency. The research informants were the greeting users, both in the nuclear family or in non-nuclear family. The data collection technique was consisted of a direct observation at the local community, interviews, and questionnaire filling (50 questions), recording, and taking notes in observing the form and usage of greetings. The result of the study indicated there are several forms of greeting used by Susupu community which included name abbreviation for addressing their biological mother and father; the foreign language influence in greeting forms; and abbreviation name for addressing the grandfather. These types of greetings were applied depending on the different generation according to the birth year. At present time, these greetings are still applied in the family also in the younger generation of the Susupu community.